Dalits in India search for a common destiny - Thorat, Sukhadeo
Documenting the status of Dalits (or scheduled castes) in contemporary India, this text charts the change in their status since independence with respect to important indicators of human development such as education level, health, housing and other social needs
Keywords: Dalits -- India -- Social conditions -- 21st century; Dalits -- India -- Economic conditions -- 21st century; Dalit; Soziale Situation; Indien